Comunicación interna y desempeño laboral de los colaboradores de comercial Nikyoli Iquitos periodo 2024 - Gomez Piña, Deysy Maritza (2024)
The present study aims to determine how internal communication influences the job performance of employees at commercial Nikyoli in Iquitos during the 2024 period. The study is descriptive-correlational with a non-experimental design, based on the observation of variables without manipulation, and was conducted over a specified period. The most important results include a Cronbach's Alpha reliability coefficient of 0.859 for the internal communication variable and 0.857 for the job performance variable, indicating a high degree of confidence in the processed data. The Pearson correlation, with a value of 0.933 and a bilateral significance level of 0.000, demonstrates a very strong positive correlation between the studied variables, confirming the hypothesis that there is a significant relationship between internal communication and job performance. In conclusion, it was found that internal communication is significantly related to the job performance of employees at commercial Nikyoli, with a Pearson correlation value of 0.933, supporting the proposed hypothesis. This study highlights the importance of internal communication as a crucial factor for improving job performance, providing a solid foundation for future management strategies in the company.